Risk Preferences and Farmers' Livelihood Strategies: A Case Study from Eastern Ethiopia. (15th January 2018) - Alemayehu, Molla; Beuving, Joost; Ruben, Ruerd
Abstract: Low‐return livelihood strategies are crucial drivers of food insecurity that may cause irreversible long‐term damage to livelihoods. Experiments and survey results were used to examine the relative importance of risk preference and socio‐economic characteristics for households' decision to engage in specific livelihood strategies in rural Ethiopia. Agricultural intensification and diversification are prevailing strategies, and farming households who participate in non‐farm activities are better off than others. Education, information access, household income and cooperative membership correlate significantly with high participation rates in non‐farm activities and on‐farm diversification. Risk preference is an especially important barrier to households' participation in these strategies. Therefore, policy interventions that help to expand farmers' asset base and reduce entry barriers to these strategies are required to improve smallholders' welfare. Copyright © 2018 John Wiley & Sons, Ltd.